Comparative Analysis of Financial Performance Before and During the Covid-19 Pandemic Using Profitability, Liquidity, Solvency and Economic Value Added (EVA) Ratios in Go Public Companies Listed on the Indonesia - Annisa Wulandari; Dina Patrisia (Universitas Negeri Padang, 2021)
The study aims to compare the company's financial performance before and during the Covid-19 Pandemic. The variables used are the ratio of profitability, liquidity, solvency and economic value added (EVA). The objects in the study are hotel, restaurant and tourism sub-sector companies listed on the Indonesia Stock Exchange. Sampling is carried out based on criteria with a sample of 25 companies with a total of 200 data observations for each variable. This research is a type of quantitative research with comparative analysis. Data analysis using comparative descriptive statistical analysis. The results showed that the Current Ratio, Quick Ratio, Cash Ratio, DER, DAR, and NPM had significant differences between before and during the pandemic. ROA, ROE and EVA did not have a significant difference between before and during a pandemic.